The Struggle of Woman Emancipation in the Movie “On The Basis Of Sex”: A Feminist Criticism - Maftuchah Dwi Agustina (ENLIT, 2022)
As stated in the theory of reception that literature including movie is a reflection of real world, this research tried to unveil social phenomenon within movie entitled “On the Basis of Sex”. In order to conduct the analysis, Marxist feminism is used as a theory. The method used in the study was descriptive qualitative method in which the movie script is the main source of the data. The result of the study showed that women did the struggle against discrimination and domination of patriarchy in some aspects, such as job and occupation, law, social environment, and cultural structure. This is a very interesting movie that brings the issue of discrimination, oppression, localization, commoditization and also the struggle to get rid of them and to establish women emancipation. The movie succeeded in portraying those social problems. The viewers of the movie could be aware of those issues. Men should be aware that they have to look at women equally. Furthermore, women also have to struggle for their right. Women should be independent. Ruth is the best example of how women should do. We have to fight against anything to establish women emancipation, even we have to fight the laws that are discriminative.